Proses komunikasi kelompok pada komunitas vespa rebelscoot wonogiri dalam menjaga solidaritas anggota - Ingga Surya Saputra (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2021)
AbstractThe purpose of this study is to describe and explain the communication process of the vespa rebelscoot community group in maintaining the solidarity of its members. this research use desciptive qualitative approach. This research use desciptive qualitative approach. Qualitative descriptive research aims to explain the phenomenon in depth through data collection. The selection of informants is carried out using the Spradley technique, in which informants are required to have certain criteria that must be considered. Data obtained by interview, direct observation and documentation study. The data analysis technique used in this study went through several stages, namely data reduction, data presentation and conclusions. The results showed that the message flow used by the Vespa Rebelscoot Community was vertical communication. Barriers to the Vespa Rebelscoot Community in communicating within the community were barriers such as communication / misunderstanding, barriers to media / communication networks. The relationship between Vespa Rebelscoot Community members in maintaining the solidarity of their group is by carrying out several activities in the community such as many outgoing agendas, touring, gathering events such as meetups with other Vespa communities, social service events. As is known, the Vespa community has a high sense of kinship through shared hobbies and common principles that uphold the value of solidarity among its members.Keywords: Group communication, Vespa Rebelscoot Community, Group Solidarity